Flat-gain wide-band erbium doped fiber amplifier by combining two difference doped fibers - Hamida, Belal Ahmed; Azooz, S. M; Jasim, Ali Abdulhadi; Eltaif, Tawfig Ahmad A.; Ahmad, Harith; Khan, Sheroz; Harun, Sulaiman Wadi (Rapid publications, 2015)
A new erbium-doped fibre amplifier (EDFA) is demonstrated using a combination of newly developed Erbium Zirconia co-doped fiber (Zr-EDF) and the commercial silica-based Erbium-doped fiber (Si-EDF) as the gain medium. Both fibers have a very high concentration of erbium ion. A compact amplifier operating in C-band region is firstly reported using a double-pass configuration. It is shown that average gains of the proposed Zr-EDF amplifier are obtained at approximately 18 dB with a gain variation of +-2 dB within C-band region. A flat-gain and wide band operation is achieved by configuring the amplifier in two stages comprising a 2 m long Zr-EDF and 9 m long Si-EDF optimised for C- and L-band operations, respectively, in a double-pass parallel configuration. A chirp fibre Bragg grating (CFBG) is used in both stages to ensure double propagation of the signal and thus to increase the attainable gain in both C- and L-band regions. At an input signal power of 0 dBm, a flat gain of 15 dB is achieved with a gain variation of less than 0.5 dB within a wide wavelength range from 1530 to 1605 nm. The corresponding noise figure varies from 6.2 to 10.8 dB within this wavelength region